The Commission on Money and Credit - Smithies, Arthur (Quarterly Journal of Economics, 1961)
Introduction, 544. — Goals and instruments, 545. — High production and employment, 550. — Economic growth, 552. — National security and government services, 556. — Assurance of equity, 558. — Price stability, 558. — Strengthening competition, 560. — The balance of payments, 563. — Co-ordination and organization, 566.